Some Bianchi-type cosmological models in a new scalar-tensor theory - Singh T.; Agrawal A.K. (My University, 2025)
Bianchi type I, III, V, VI0, and Kantowski-Sachs type models have been investigated in a scalar tensor theory developed by Saez and Ballester (1985) and Saez (1985). The dynamical behaviour of the models has also been analyzed. © 1991 Kluwer Academic Publishers.